SISTEM INFORMASI PELAYANAN PERIZINAN DAN SURAT REKOMENDASI PADA KANTOR CAMAT PARIAMAN TENGAH BERBASIS WEB - Arman Arman; Ratih Purwasih; Nelfira Nelfira; Rajab Rajab; Richel Maulana Alberi Ananda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
A website-based public service information system is made so that the public can easily find out what activities are in Central Pariaman District. In law number 25 of 2009 concerning public services, it is an activity or series in the context of fulfilling service needs in accordance with statutory regulations for every citizen and resident of goods, services or administrative services provided by public service providers. Central Pariaman District is one of the sub-districts in Pariaman City, West Sumatra Province, the problems include information on licensing services and recommendations given to the community still using banner billboards placed on information boards and located in the Pariaman sub-district office There is no licensing service and recommendation letters digitally because the service is carried out at the Pariaman Tengah sub-district office. The use of existing computerized devices is not optimally used in processing correspondence archives which still use paper in recording licensing reports and letters of recommendation. 16 Types Only 5 are taken consisting of Building Permits (IMB), IUMK Applications (Micro and Small Business Permits). Recommendation Statement of Not Married, Recommendation of Statement of Good Practice, Recommendation of Statement of Death. This research uses the waterfall method and the PHP and Mysql programming languages. Conclusions that provide information that supports the management of permits and letters of recommendation by the community. processing of licensing data and letters of recommendation Can improve and provide licensing services and letters of recommendation better than before to the community.